P1466Leadless pacemaker mid and long term follow-up in a single center-study. (18th June 2020) - Martinez Sande, J L; Garcia-Seara, J; Gonzalez-Melchor, L; Cacho-Antonio, C E; Fernandez-Lopez, X A; Rodriguez-Manero, M; Abou-Jokh, C; Lopez-Canoa, J N; Gonzalez-Juanatey, J R
Abstract: Introduction and objectives: Initial results of Leadless pacemakers (LPM) has been promising in worldwide, nevertheless there are still no long term experience published, so the objective of our study was to evaluate electrical parameters at mid  and long term follow-up, describing as well total complications and mortality in a single center-study. Methods:   This was a prospective, observational clinical trial that included 183 consecutive patients, with an indication for a single-chamber pacemaker implantation. Results:   All successful implantation included a total of 183 patients with a mean age of 79, 2 ±6, 6 years (range 54-93y/o); 111 (60, 6%) were men and more frequent rhythm was permanent atrial fibrillation (160), including those in which a node ablation was performed in the same procedure (22). Clinical and echocardiographyc characteristics are described in table 1.Mean follow-up was of 26 ±10 months including: 64 patient at 24 months, 46 at 36 months and 7 patients at 48 months. Electrical parameters are represented in figure 1, which were stable and flawless at long term follow-up.  Total complications were 3, 3%, with only 2 patient requiring surgery for resolution (1, 7%), and all were acute during LPM implantation. A total of 17 patients (9, 3%) died with no relation to pacemaker.  Conclusions: In our experience, leadless pacemakers electrical performance continues stable, appropriate at long term follow-up, and no other complications developed.